A Study of the Association between Corporate Governance Norms and Development of the Life Insurance Sector: Examining the Impact of Corporate Governance Norms on the Development of the Life Insurance Sector (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Private or public insurance firms both play an important part in India's economy. Private and government insurance firms in India are expanding the insurance industry, and as a result, India's fundamental infrastructure is growing quickly, and its citizens are benefiting from improved insurance plans. Insurance firms in India provide and arrange for policyholders in accordance with their requirements. A company's corporate governance offers the framework for identifying and selecting techniques that will help it achieve its objectives via monitoring and implementation. The board should always support the company when there is a genuine concern for its investors because good corporate governance gives the proper mechanism to the board, The Indian life insurance sector has a pressing need for corporate governance. The development of life insurance businesses is impacted by corporate governance standards. And life insurance, in terms of corporate governance Insurance in India has a long history.